Development of a web database portfolio system with PACS connectivity for undergraduate health education and continuing professional development - Ng, Curtise Kin Cheung; White, P.; McKay, Jan (Elsevier Ireland Ltd, 2009)
Increasingly, the use ofweb database portfolio systems is noted in medical and health education,and for continuing professional development (CPD). However, the functions of existingsystems are not always aligned with the corresponding pedagogy and hence reflection isoften lost. This paper presents the development of a tailored web database portfolio systemwith Picture Archiving and Communication System (PACS) connectivity, which is based onthe portfolio pedagogy.Following a pre-determined portfolio framework, a system model with the componentsof web, database and mail servers, server side scripts, and a Query/Retrieve (Q/R) broker forconversion between Hypertext Transfer Protocol (HTTP) requests and Q/R service class ofDigital Imaging andCommunication in Medicine (DICOM) standard, is proposed. The systemwas piloted with seventy-seven volunteers.A tailored web database portfolio system (http://radep.hti.polyu.edu.hk) was developed.Technological arrangements for reinforcing portfolio pedagogy include popup windows(reminders) with guidelines and probing questions of ‘collect’, ‘select’ and ‘reflect’ onevidence of development/experience, limitation in the number of files (evidence) to beuploaded, the ‘Evidence Insertion’ functionality to link the individual uploaded artifacts withreflective writing, capability to accommodate diversity of contents and convenient interfacesfor reviewing portfolios and communication. Evidence to date suggests the systemsupports users to build their portfolios with sound hypertext reflection under a facilitator’sguidance, and with reviewers to monitor students’ progress providing feedback andcomments online in a programme-wide situation.